INVESTIGATING THE LEARNING CONDITIONS IN THE ONLINE-BASED TEACHER-LEARNING COMMUNITIES IN INDONESIA - Wawan Krismanto; Abdul Halik; Yonathan S. Pasinggi; Ritha Tuken (IJIET (International Journal of Indonesian Education and Teaching), 2026)
The learning community in Indonesia is snowballing among teachers. The problem is that only a few teacher-learning communities are consistence and intense in carrying out teacher-learning activities. This study aims to investigate how the learning conditions in online-based teacher-learning communities in Indonesia consistently carry out teacher-learning activities. The research design uses a qualitative approach with the case study method, and the research framework uses a qualitative e-research framework. Various data were obtained through interviews with eight teachers, documentation studies, and observation of teacher learning activities through online-based teacher-learning communities. The results show that some management of learning conditions is required to organize professional learning for teachers through online-based teacher-learning communities. Namely: 1) learning activities are inclusive and sustainable; 2) the characteristics of the learning participants are individuals who have a high initiative to re-learn; 2) the characteristics of learning topics according to the needs and problems of teachers; 3) the characteristics of the speakers are from the teachers themselves (fellow teachers); 4) learning objectives are focused on improving teachers' teaching practice skills; and 5) there is a mapping of learning barriers that are managed during the learning process.